Spontaneously Regressing Neonatal Oral Aphthous Ulceration of the Palate - Sandara Wayangi Madurapperuma; Andra Hennadige Heshan Malinga Jayaweera; Ruwan Duminda Jayasinghe (Hindawi Limited, 2021)
Background. Neonatal oral aphthous ulceration of the palate also known as Bednar's aphthae is not an uncommon presentation. They clinically present as spontaneously regressing, shallow, and symmetrical ulcers on the posterior palate of newborns from 2 days up to 6 weeks of age. Case Presentation. We, herein, report a case of a one-month-old baby girl who presented with an ulcer in the posterior palate and intermittent mild fever. The patient was admitted and monitored in the ward. Haematologic investigations disclosed features of ongoing infection. Nasogastric feeding was commenced to avoid any irritation of the ulcer, and glycerine was applied on the ulcer. Antibiotic therapy was continued because of the intermittent mild fever. The lesion healed spontaneously within one week, and fever subsided afterwards. Currently, the patient is faring healthily without any complications. Conclusion. Although Bednar's aphthae is not a rare presentation, clinicians are often met with a diagnostic dilemma due to the alarming clinical presentation of this condition. Therefore, it leads to overinvestigation and overtreatment. With this case report, we would like to highlight the importance of being aware of this condition to provide the patients with the appropriate treatment.